The Legal Politics Harmonization of Sustainable Agricultural Policy - Ermanto Fahamsyah; Ruetaitip Chansrakaeo (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
Sustainable agriculture is one of the future-oriented legal policies. In this case, agriculture is oriented to be preserved, especially for future generations. Problems occur when various laws and regulations governing sustainable agricultural law policies are disharmonies even though they are substantially interrelated. This study aims to initiate legal politics of harmonization of sustainable agricultural policies. This research is normative legal research that focuses on analyzing legal issues. Analysis of legal issues is essential in legal research oriented to prescriptions or legal solutions to the problems being discussed. The approach in this study uses a statutory approach and a conceptual approach. The results of the study confirm that the implications of disharmony of sustainable agricultural law policies in various laws and regulations in Indonesia need to make legal harmonization in planning, formulating, and evaluating legislation. Future improvements to the legal politics of sustainable agriculture in Indonesia can be carried out by harmonization of legal policies related to sustainable agriculture by revising the PP PBP to include sustainable agriculture as one of its regulatory substances.